Impact of Corporate Governance and Ownership Structure on the Profitability of Nepalese Commercial Banks - Yadav, Reema; Karki, Resha; K.C., Samprabha; Mahato, Sandip Kumar; Paudel, Sangita; Neupane, Santoshi (Nepalese Journal of Finance, 2025)
The study examines the impact of corporate governance and ownership structure on the profitability of Nepalese commercial banks. Return on assets and net interest margin are selected as the dependent variables. The selected independent variables are board size, leverage, gender diversity, board independence, audit committee size, and institutional ownership. The study is based on secondary data of 13 commercial banks with 104 observations for the period from 2015/16 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance and ownership structure on the profitability of Nepalese commercial banks. The study showed that board size has a negative impact on return on assets and net interest margin. It indicates that higher the board size, lower would be the return on assets and net interest margin. Similarly, leverage has a negative impact on return on assets and net interest margin. It indicates that higher the leverage, lower would be the return on assets and net interest margin. However, gender diversity has a positive impact on return on assets and net interest margin. It indicates that higher the gender diversity in the boards, higher would be the return on assets and net interest margin. Likewise, board independence has a positive impact on return on assets and net interest margin. It indicates that increase in board independence leads to increase in return on assets and net interest margin. Further, audit committee size has a positive impact on return on assets and net interest margin. It indicates that higher the audit committee size, higher would be the return on assets and net interest margin. In addition, institutional ownership has a positive impact on return on assets and net interest margin. It indicates that higher the institutional ownership, higher would be the return on assets and net interest margin.